Spontaneous subdural empyema in falciparum malaria : a case study - S. Dwarakanath, A. Suri , A.K. Mahapatra (Journal of Vector Borne Diseases, 2004)
Clinical history : Malaria is one of the most common diseases in the tropical countries. Cerebralmalaria is usually a diffuse symmetric encephalopathy with focal signs being unusual.Methods : We present a three-year old girl lapsing into unconsciousness following a seizure whileundergoing treatment for malaria. Imaging revealed a large heterogenous density, left hemisphericacute subdural haematoma with brain herniation. Investigations revealed anaemia, thrombocytopeniaand positive peripheral blood smear for falciparum malaria.Results : Treatment involved surgical evacuation of the clot and the associated subdural empyema,intravenous quinine and antibiotics.Conclusion : This is the second case report of spontaneous subdural empyema in complicatedfalciparum malaria and highlights a rare but surgically manageable complication.